Antiinflammatory and Antimicrobial Property of Dioscorea deltoidea L from Nepal - Rajendra Gyawali, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
Antiinflammatory and Antimicrobial Property of Dioscorea deltoidea L from Nepal